(untitled) (CIPEEX, 2022)
CRIMINAL LIABILITY FOR LEGAL ENTITIES IS DEALT WITH IN THE ENVIRONMENTAL CRIMES LAW NUMBER 9.605 / 98, BUT THE FEDERAL CONSTITUTION ALREADY STATES IN ITS TEXT THAT EVERYONE IS ENTITLED AND ARE RESPONSIBLE FOR THE PROTECTION OF THE ENVIRONMENT, INCLUDING AS LEGAL ENTITIES. THE MAIN OBJECTIVE OF THE WORK IS TO DEMONSTRATE HOW LAW NO. 9,605 / 98 WAS CREATED, HOW IT IS APPLIED, AND HOW LEGAL ENTITIES ARE HELD RESPONSIBLE WHEN THEY COMMIT ENVIRONMENTAL CRIMES, AS WELL AS TO VERIFY THE MEANS OF PUNISHMENT APPLICABLE TO THESE PEOPLE, AND HOW IT IS THE PROCEDURAL PROGRESS AND ITS DUE COMPETENCES, IN ADDITION TO DEMONSTRATING IN PRACTICE HOW THESE CONDEMNATIONS WERE MADE, HOW THE SENTENCES ARE SERVED AND HOW LAW NO. 9.605 / 98 HAS BEEN APPLIED TO THE SITUATIONS. AIMING THE AWARENESS OF THE POPULATION AND ESPECIALLY OF LEGAL ENTITIES TO PROTECT AND USE SOURCES THAT DO NOT HARM THE ENVIRONMENT, KEEPING IT ECOLOGICALLY BALANCED AND PRESERVED.